A New Spider Species of the Genus Harpactea (Araneae, Dysderidae) from Türkiye - Kunt, K. B.; Özkütük, R. S.; Yağmur , E. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
Harpactea ulgen sp. n. is described based on both sexes from Türkiye. The new species belongs to the rubicunda species group as defined by Deeleman-Reinhold (1993) and is closely related to the Turkish endemic H. ballarini Kunt, Özkütük & Elverici, 2013.